Reinforcing the Ultimum Remedium Principle in Environmental Law Enforcement: A Three-Layered Approach Under Law No. 32 of 2009 - I Gusti Bagus Suryawan; I Putu Ngurah Aryana; Yohanes I Wayan Suryadi; M. Ngurah Arya Yogie Krsna; Mirela Maria Ribeiro Guterres (Jurnal Hukum, 2025)
Environmental law enforcement in Indonesia, particularly under Law No. 32 of 2009 on Environmental Protection and Management, faces persistent challenges in applying the principle of ultimum remedium—treating criminal sanctions as a last resort. This study aims to evaluate the effectiveness of non-criminal sanctions, namely administrative and civil measures, as prerequisites to criminal enforcement in environmental cases. Using a normative juridical method and descriptive-analytical approach, the research analyzes statutory regulations, judicial decisions, and enforcement practices in pollution cases, including hazardous and toxic waste violations. The findings reveal that administrative and civil sanctions remain weak due to limited supervision, lengthy civil procedures, and inadequate compensation mechanisms. Additionally, poor institutional coordination and limited enforcement capacity hinder the transition to criminal sanctions. Community involvement is also underutilized in supporting legal accountability. The study concludes that a more structured three-layered enforcement approach—integrating administrative, civil, and criminal mechanisms—is needed to uphold environmental justice. Strengthening institutional capacity and aligning reparative and retributive principles are essential to ensure the ultimum remedium principle operates effectively. These findings contribute to legal reform efforts and the development of sustainable environmental governance in Indonesia.